Practical Application of Oxygen Augmentation Observation in the Process of Unsealing Fire Zone: Case study of Yu Wu coal mine in China. Issue 5 (September 2022) - Wu, Bing; He, Binbin; Zhao, Chenguang; Lei, Baiwei
It is very important to unseal the closed coal mine fire zone safely. Although the fire source disappears in the closed fire zone, it is uncertain whether there are still have high-temperature ignition points, and there is a risk of fire or even explosion again after unsealing. To ensure that the closed fire zone can be unsealed successfully at one time, the study puts forward the method of oxygen augmentation observation to understand the combustion state of the closed fire zone in underground coal mine from the perspective of gas analysis technology. When the mine fire is detected to be extinguished, the method is to inject 8–12% oxygen into the fire area, and the fire area shall be monitored for 2 weeks to determine whether the fire area is completely extinguished. The accuracy and practicality of the method of oxygen augmentation observation are verified by comparing and analyzing the difference results generated by two oxygen augmentation observations in closed zone of Yuwu Coal Mine. In this paper, the use conditions of unsealing in fire zone, detailed methods and steps in the whole process of unsealing and emergency rescue plan are given. The research results can provide valuable reference for one-time safe unsealing of fire zone during the process of disaster relief.